2017
DOI: 10.1371/journal.pone.0168183
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics Reveals Ecophysiological Effects of Light and Silver Stress on the Mixotrophic Protist Poterioochromonas malhamensis

Abstract: Aquatic environments are heavily impacted by human activities including climate warming and the introduction of xenobiotics. Due to the application of silver nanoparticles as bactericidal agent the introduction of silver into the environment strongly has increased during the past years. Silver ions affect the primary metabolism of algae, in particular photosynthesis. Mixotrophic algae are an interesting test case as they do not exclusively rely on photosynthesis which may attenuate the harmful effect of silver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“… 2015 ; Beisser et al . 2017b ). As shifts in the prevailing mode of nutrition usually require more than 24 h, a switch of nutritional mode within mixotrophs is no subject of a diurnal variation (Sanders, Porter and Caron 1990 ).…”
Section: Introductionmentioning
confidence: 99%
“… 2015 ; Beisser et al . 2017b ). As shifts in the prevailing mode of nutrition usually require more than 24 h, a switch of nutritional mode within mixotrophs is no subject of a diurnal variation (Sanders, Porter and Caron 1990 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the functional level a test for differential expression reveals 34 KEGG orthologous genes that differ significantly (FDR <0.1) between the two groups and show an enrichment of photosynthesis pathways. It is known that silver ions affect the primary metabolism in particular photosynthesis by direct interference [ 53 , 56 ]. On the other hand, it has been shown that for low concentrations of silver green algae grows is increased as observed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…On the functional level a test for differential expression reveals 34 KEGG orthologous genes that differ significantly (FDR < 0.1) between the two groups and show an enrichment of photosynthesis pathways. It is known that silver ions affect the primary metabolism in particular photosynthesis by direct interference [52,53]. On the other hand, it has been shown that for low concentrations of silver green algae grows is increased as observed in Figure 7 A [54].…”
Section: Discussionmentioning
confidence: 99%